Comparative Analysis of E-banking Services for Individual Clients in Poland - Chmielarz, Witold (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The main goal of the paper is the analysis of the use of Internet banking services by individual clients in Poland at the beginning of 2007. First, the market of electronic services in Poland is described. Next, offers of Internet banking services of four banks: mBank, Inteligo, VW Bank and Toyota Bank are compared according to various methodologies. Finally, the author draws conclusions from this comparison concerning methodological correctness of the conducted research.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 30-39